The mechanical performance of tile based on plastic waste (PW) mixed wood waste (MWW) - Marsi, Noraini; Huzaisham, Nur Athirah; Muhd Rus, Anika Zafiah; Lecthumanan, Thineshnaidu; Mahmood, Salwa; Masrol, Shaiful Rizal; Abdul Rashid, Azrin Hani; Mohd Fodzi, Muhammad Haikal; Thanasingam, Rupashinii (American Scientific Publishers, 2020)
Demand for recycling product like plastics, papers, metals and alternative materials will increase due to its numerous applications particularly on business. Recently analysis estimates that 8.3 billion metric tons of plastic has been made within the 65 years production of plastics began. Approx-imately 4.9 billion tons has already been terminated up in lowland or polluting the setting. This project research is to study the mechanical performance of tile based on plastic waste (PW) mixed with wood waste (WW). The objective is to evaluate the mechanical properties and to determine the optimum ratio of PW reinforced WW for tile application. In this study, there are four types of com-posites ratio of PW reinforced WW which are 1.0 PW:2.0 WW, 2.0 PW:2.0 WW, 3.0 PW:2.0 WW, and 4.0 PW:2.0 WW. The processes involved grinding, sizing and mixture process. Firstly, the PW and WW were grinded by using Grind Machine with the speed of 300 rpm. Then, the composition of PW and WW were mixed together with special resin by ratios into square aluminum tray with dimension of 26 cm× 26 cm and thickness of 0.5 cm. The samples were cured for 48 hours at room temperature (27 C). The maximum tensile strength was observed that the ration of 3.0 PW:2.0 WW loading produced the highest strength at 313.81 N. The bending test exhibited 2069.20 N for the ratio of 3.0 PW:2.0 WW. For impact test, 3.0 PW:2.0 WW can withstand the maximum stress at 1.67 kJ/m2. 3.0 PW:2.0 WW showed lower density of 1.070 g/cm3 and higher porosity value of 0.05%. It clearly shows that fiber matrix bonding PW:WW in distribution special resin form a strong adhesive bond at ratio of 3.0:2.0 with magnification of 10× by using Optical Microscopes Image. In conclusion, the composition ratio of PW:WW revealed that 3.0 ratio of PW reinforced with 2.0 ratio of WW produce optimum ratio for tile application.